1991
DOI: 10.1128/iai.59.8.2750-2757.1991
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Streptococcus pneumoniae type 14 capsular polysaccharide: influence of carriers and adjuvants on isotype distribution

Abstract: This project investigated the effects of novel carriers and adjuvants on the isotype of murine immunoglobulin G (IgG) antibody to pneumococcal capsular polysaccharide type 14 (S14PS). S14PS conjugated to bovine serum albumin induced a weak antibody response which was 100% IgGl following injection without adjuvant. The same polysaccharide conjugated to flagella of Salmonella typhi induced an antibody response which was 88% IgG3. S14PS-bovine serum albumin was injected with block copolymer L121 or Quil A in squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Both humoral and cellular immune responses are necessary for an effective malaria vaccine against blood-stage parasites (29,40). One way to influence the host immune responses to an antigen is by the use of adjuvants (1,19,23,25,45). Immunization studies with C-terminal fragments of P. falciparum MSP-1 in primate malaria models showed that no protection was induced when an Escherichia coli-expressed 19-kDa antigen was formulated in aluminum hydroxide (alum) and liposomes (5).…”
mentioning
confidence: 99%
“…Both humoral and cellular immune responses are necessary for an effective malaria vaccine against blood-stage parasites (29,40). One way to influence the host immune responses to an antigen is by the use of adjuvants (1,19,23,25,45). Immunization studies with C-terminal fragments of P. falciparum MSP-1 in primate malaria models showed that no protection was induced when an Escherichia coli-expressed 19-kDa antigen was formulated in aluminum hydroxide (alum) and liposomes (5).…”
mentioning
confidence: 99%
“…As with other polysaccharides, covalent attachment of Pnl4 to a protein conferred enhanced immunogenicity and T-cell dependence (booster responses [31]). van de Wijgert et al prepared conjugates of Pnl4 with bovine serum albumin or the flagella of Salmonella typhi by a scheme similar to one described by us (9,38). Injection of 100 ,ug of these Pnl4 conjugates elicited serum antibodies in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The development of polysaccharide protein conjugates for prevention of systemic infections caused by Haemophilus influenzae type b serves as a precedent for making conjugates of polysaccharides of other capsulated pathogens (31). This technology has been extended to improve the immunologic properties of other polysaccharides of medically important organisms such as Streptococcus pneumoniae (5,9,10,25,26,31,38,39). Since the objective is to provide protection against many capsulated bacterial pathogens of infants and children, investigators have used established vaccines such as diphtheria and tetanus toxoids or potentially protective antigens such as the toxoids of Pseudomonas aeruginosa exotoxin A and pneumococcal hemolysin (3,7,23,24).…”
mentioning
confidence: 99%
“…It is evident from passive transfer experiments that protection might not be possible with a mere increase in antiporin antibody titre alone. Several studies [14,[25][26][27] indicate the strong influence of adjuvants on antibody isotypes generated in vivo. Hence, the subclasses of antibodies induced were analysed to understand the importance of quality of antibodies induced.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been well established that antibody isotype is an important parameter in determining the protective efficiency of vaccines against invading pathogens. The vaccine efficacy thus depends not only on the titre but also on the class and isotype of antibodies induced [14]. Therefore, it is important to analyse and compare the antiporin IgG subclass antibodies induced by various porin-immunopotentiator preparations in terms of protection against murine Salmonellosis.…”
Section: Introductionmentioning
confidence: 99%